2014
DOI: 10.5694/mja13.11153
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of Clostridium difficile infection, Australia, 2011–2012

Abstract: Objectives: To report the quarterly incidence of hospital‐identified Clostridium difficile infection (HI‐CDI) in Australia, and to estimate the burden ascribed to hospital‐associated (HA) and community‐associated (CA) infections. Design, setting and patients: Prospective surveillance of all cases of CDI diagnosed in hospital patients from 1 January 2011 to 31 December 2012 in 450 public hospitals in all Australian states and the Australian Capital Territory. All patients admitted to inpatient wards or units in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
85
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 16 publications
(23 reference statements)
5
85
1
Order By: Relevance
“…4,5,7,14-16 New research from Australia has shown the proportion of community-onset cases of CDI to have increased significantly in recent years, to 26%. 16 The strong association with prior antibiotic use in hospitalacquired CDI is not seen as commonly in the community-onset group and cannot be relied upon to predict cases. Thirty-four percent of community-onset cases did not have prior antibiotic use as a risk factor, which is similar to the findings of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,7,14-16 New research from Australia has shown the proportion of community-onset cases of CDI to have increased significantly in recent years, to 26%. 16 The strong association with prior antibiotic use in hospitalacquired CDI is not seen as commonly in the community-onset group and cannot be relied upon to predict cases. Thirty-four percent of community-onset cases did not have prior antibiotic use as a risk factor, which is similar to the findings of other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that HCA CDI are associated with prolonged hospitalization, high mortality and adverse outcome [1,2]. It has now been found to be an increasingly important infection in a community setting as well [3], particularly in Europe [4,5], North America [6e8], Australia [9,10], and Asia [11]. In this setting, CDI is often seen in young patients who were previously thought to be at low-risk for developing the infection e.g.…”
Section: Introductionmentioning
confidence: 99%
“…CDI reached an epidemic state in many developed countries with high incidence and severe disease in healthcare settings and in the community. In some regions of the world, including Australia, community-associated CDI (CA-CDI) now accounts for up to 25% of all cases (Slimings et al, 2014; Bloomfield and Riley, 2016). …”
Section: Introductionmentioning
confidence: 99%